Pre-irrigation and seeding of wheat (Triticum aestivum) after clusterbean on yield, water productivity and soil properties - SINGH, Y P (The Indian Journal of Agricultural Sciences, 2020)
On farm research was conducted during winter (rabi) of 2014-17 to study the effect of dry seeding (DS) of wheat (Triticum aestivum L.) for early establishment after harvest of clusterbean and irrigation for germination compared with conventional practice of pre-irrigation (PI) for seeding in three tillage practices, viz. conventional (CT), minimum (MT), zero-till (ZT). Pooled results indicated that the seeding of wheat with ZT method in DS conditions significantly influenced the growth parameters; yield, economic benefits, energy output and water productivity (WP) over conventional practices. The grain yield of wheat was increased by 5.1-11.6% with DS and 5.0-10.7% with ZT over conventional practices, respectively. The significantly higher production cost was recorded with CT compared to ZT. Out of total production cost, higher expenditure (22.2%) on tillage and seeding with CT, whereas with MT and ZT was 11.5% and 3.7%, respectively. The significantly higher energy input and total water use (TWU) was required with CT over ZT. The additional 263 m3/ha TWU was saved and WP increased by 17.5% with DS, while 234 m3/ha TWU was saved and WP increased by 16.4% with ZT over conventional practices, respectively. After harvest of third wheat crop, organic carbon, infiltration rate, available N, P, K and Zn were significantly increased, whereas bulk density was lowest with ZT over CT. The study reveals that improved yield, economic benefits, WP, soil physicochemical properties, saved energy and resources with DS of wheat after clusterbean harvest with ZT seeding and irrigation for germination in late sown conditions.